Abnormal amplitude of spontaneous low-frequency fluctuation in children with growth hormone deficiency: A resting-state functional magnetic resonance imaging study. (18th January 2021) - Zhang, Fanyu; Hua, Bo; Wang, Tengfei; Wang, Mei; Ding, Zhong xiang; Ding, Ju-Rong
Highlights: We examine the spontaneous neural activity in children with GHD using ALFF analysis. Several regions showed abnormal ALFF values in children with GHD compared to HCs. Altered ALFF may account for the abnormal cognition and behavior related to GHD. Our findings aid to understand the pathophysiological mechanisms underlying GHD. Abstract: Growth hormone deficiency (GHD) is a developmental disorder caused by the partial or complete deficiency of growth hormone secreted by the pituitary gland, or its receptor. Patients with GHD are characterized by short stature, slow growth, and certain cognitive and behavioral abnormalities. Previous behavioral and neuroimaging studies indicate that GHD might affect the brain functional activity associated with cognitive and behavioral abilities. We thus investigated the spontaneous neural activity in children with GHD using amplitude of low-frequency fluctuation (ALFF) analysis. ALFF was calculated based on resting-state functional magnetic resonance imaging (rs-fMRI) data in 26 children with GHD and 15 age- and sex-matched healthy controls (HCs). Comparative analysis revealed that the ALFF of the right lingual gyrus and angular gyrus were significantly increased, while the ALFF of the right dorsolateral superior frontal gyrus, the left postcentral gyrus, superior parietal gyrus and middle temporal gyrus were significantly decreased in children with GHD relative to HCs. These findings support the presence of abnormal brain functional activity in children with GHD, which may account for the abnormal cognition and behavior, such as aggression, somatic complaints, attention deficits, and language withdrawal. This study provides imaging evidence for future studies on the pathophysiological mechanisms of abnormal behavior and cognition in children with GHD.